2017
DOI: 10.1038/nrneurol.2017.45
|View full text |Cite
|
Sign up to set email alerts
|

Human induced pluripotent stem cells for modelling neurodevelopmental disorders

Abstract: Currently, we have a poor understanding of the pathogenesis of neurodevelopmental disorders, owing to the fact that post-mortem and imaging studies are only capable of measuring the postnatal status quo and offer little insight into the processes that give rise to the observed outcomes. Human induced pluripotent stem cells (hiPSCs) in principle should prove powerful in elucidating the pathways that give rise to neurodevelopmental disorders. HiPSCs are embryonic stem cell-like cells that can be derived from som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
108
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 197 publications
(165 reference statements)
0
108
0
6
Order By: Relevance
“…Without detailed knowledge of the underlying genetics, patient-derived hiPSCs after in vitro differentiation provide a nearly unlimited supply of disease-relevant somatic cells for in vitro modelling that carry all the genetic elements implicated in disease development. Comparing neurons derived from patients with schizophrenia or autism spectrum disorders to age-matched unaffected individuals (Figure 1B) identified disease-relevant phenotypic changes providing proof-of concept to modeling sporadic diseases (reviewed in (Ardhanareeswaran et al, 2017; Hoffman et al, 2018). While initially surprising, considering the patients’ genetic heterogeneity, such robust disease-associated phenotypes may result from diverse genetic variants that converge on common developmental pathways such as cortical development, synaptic function and epigenetic processes (Hoffman et al, 2018).…”
Section: Hpsc Models Of Complex Diseases - Conventional Approachmentioning
confidence: 89%
See 1 more Smart Citation
“…Without detailed knowledge of the underlying genetics, patient-derived hiPSCs after in vitro differentiation provide a nearly unlimited supply of disease-relevant somatic cells for in vitro modelling that carry all the genetic elements implicated in disease development. Comparing neurons derived from patients with schizophrenia or autism spectrum disorders to age-matched unaffected individuals (Figure 1B) identified disease-relevant phenotypic changes providing proof-of concept to modeling sporadic diseases (reviewed in (Ardhanareeswaran et al, 2017; Hoffman et al, 2018). While initially surprising, considering the patients’ genetic heterogeneity, such robust disease-associated phenotypes may result from diverse genetic variants that converge on common developmental pathways such as cortical development, synaptic function and epigenetic processes (Hoffman et al, 2018).…”
Section: Hpsc Models Of Complex Diseases - Conventional Approachmentioning
confidence: 89%
“…Following in vitro differentiation, patient-derived hiPSCs provide disease-relevant somatic cells, which carry all the genetic elements implicated in the disease reflecting the genetic spectrum of the patient population. While discussing all of these studies is beyond the scope of this work, excellent recent reviews summarize hiPSC diseases models for neurodevelopmental (Ardhanareeswaran et al, 2017), neuropsychiatric (Hoffman et al, 2018) and neurodegenerative diseases including Alzheimer’s disease (Sullivan and Young-Pearse, 2017) and Parkinson’s disease (Shi et al, 2016; Zhang et al, 2017)), motor neuron and Huntington’s disease. The spectrum of phenotypes, which can be assessed in hiPSC-based in vitro models include a wide range of molecular, metabolic, cellular and electrophysiological analysis.…”
Section: Hpsc-based Models For Monogenetic Diseasesmentioning
confidence: 99%
“…It is still difficult to harvest sufficient numbers of cells from a living donor to create stem cell lines. Creating induced pluripotent stem (iPS) cell lines from adult tissues like skin and blood can allow researchers to recapitulate changes that occur during development and study why development of some tissues does not occur normally in TS (Ardhanareeswaran, Mariani, Coppola, Abyzov, & Vaccarino, 2017). …”
Section: Definition and Backgroundmentioning
confidence: 99%
“…Dissociated cultures of neurons allow for close monitoring of their individual development throughout differentiation; however, their maturation and survival is limited compared to neurons developing in the embryonic brain, likely due to the lack of appropriate support in in vitro cultures 26,27 . Moreover, disease phenotypes affecting synapse formation, dendritic retraction and neuronal migration 28,29 , which may only arise from interactions between cells and their environment, may be lost in these two-dimensional cultures.…”
Section: Generation Of Cerebellar Neurons Using Human Ipscsmentioning
confidence: 99%
“…Indeed, transcriptomic analysis of other iPSC-derived neuronal models has revealed that the generated neurons are still in an embryonic state, despite the fact that individual neurons have been stained for mature markers (reviewed in 29 ). Such immature cells may be beneficial for the study of developmental aspects of disease.…”
mentioning
confidence: 99%